A New Fractional Subequation Method and Its Applications for Space-Time Fractional Partial Differential Equations. (31st July 2013) - Meng, Fanwei; Feng, Qinghua
Abstract : A new fractional subequation method is proposed for finding exact solutions for fractional partial differential equations (FPDEs). The fractional derivative is defined in the sense of modified Riemann-Liouville derivative. As applications, abundant exact solutions including solitary wave solutions as well as periodic wave solutions for the space-time fractional generalized Hirota-Satsuma coupled KdV equations are obtained by using this method.